Izražanje spola v frazeologiji - Jakop, Nataša (Slavistična revija, 2019)
In the article I describe the characteristics of gender of nominal phrasemes containing the semantic component "human." I defined the phrasemes by gender, including the subgender of animacy and human, and their referential gender on the basis of their definitions in dictionaries and their textual realizations. The comparison revealed that non-actualized definitions of gender-marked phrasemes in dictionaries maintain or intensify certain sexually-related stereotypes about men and women.
Keywords: grammatical gender; naravni spol; nominal phrasemes; podspol človeškosti; podspol živosti; referenčni spol; referential gender; samostalniški frazemi; sex gender; Slovenian language; slovenščina; slovnični spol; subgender of animacy; subgender of human